(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Diseases of the musculoskeletal system in children are among the most common health problems among schoolchildren. The incidence of this The prevalence of scoliosis among students fluctuates between 7.4% and 54%, and during schooling the prevalence of scoliosis among students increases by 3.5-4 times. A comparative analysis of preventive examination data over 10 years shows a threefold increase in the prevalence of scoliosis among first-graders (from 7.4% to 22.7%), among 4th-5th grade students by 2.4 times (from 14.1% to 34.6%); among 15-year-old students by 1.7 times (from 32% to 54.4%; among 11th grade senior students - by 1.4 times from 32.3% to 45.45%). Posture disorders in schoolchildren are even more common and occur 3-6 times more often than scoliosis. The prevalence of these functional disorders increases in children from the 1st grade to the transition to subject-based learning by 5-6 times (from 18-22% to 85-137.9%). In adolescence, the frequency of posture disorders decreases to 84.3-94.7%, and the number of children with scoliosis increases first of all.